In-vitro degradation and toxicological assessment of pulsed electric fields crosslinked zein-chitosan-poly(vinyl alcohol) biopolymeric films. (January 2020) - Giteru, Stephen G.; Cridge, Belinda; Oey, Indrawati; Ali, Azam; Altermann, Eric
Abstract: We investigated the in vitro degradation and cytotoxic effects of edible films developed from pulsed electric fields (PEF) treated zein-chitosan-poly(vinyl alcohol) dispersions at specific energy 60–70, 385–400, and 620–650 kJ/kg. The degradation was evaluated using both simulated gastro-intestinal electrolyte solutions (SGES) and enzyme hydrolysis. The results of ortho -phthaldialdehyde (OPA) test indicated that the chemical breakdown of the films in SGES and enzyme increased with degradation time, but the product's features were unmodified. The Fourier Transform Infrared spectroscopy (FTIR) data showed enhancement of zein and chitosan transformation from ordered helices to β -sheet conformation. Relative cell survival rates of Hepa-1c1c7 cells investigated using 3-[4, 5- dimethylthiazol-2-yl]-2, 5-diphenyltetrazolium bromide) showed that the survival remained higher than 70% in both the supernatant and the residue of the SGES degraded samples and the supernatant from enzyme hydrolysis, which suggested that there was no significant toxicity of the films in the tested system. Although the residue from pancreatic digestion (240 min) (i.e. undigested films and a cocktail of digestion enzymes) expressed cytotoxicity activity, there was limited evidence of direct toxicity of the films. The findings of the study demonstrate the potential for PEF modified zein-chitosan-poly(vinyl alcohol) films as value-added biomaterials for the application in edible food packaging. Graphical abstract: Image 1 Highlights: PEF processing induces conformational changes in the structure of the zein in ZCP films. Low-intensity PEF enhances the stability of ZCP films against electrolyte and enzyme degradation. Low-intensity PEF enhances the growth of Hepa-1c1c7 cells on degraded ZCP films. PEF shows no influence on the cytotoxicity of in vitro digested ZCP films.